Direct and Indirect Effects of Climate Change Perceptions on Fishermen's Catches: A Path Analysis Approach - Zumrotun Ni’mah; Moh. Wahyudi Priyanto; Setiani Setiani (Fakultas Perikanan UCM, 2026)
The fisheries sector contributes to food security, poverty alleviation, and the improvement of welfare. However, fishermen face serious challenges due to climate change, which disrupts fishing activities. This issue is also experienced by fishermen on Madura Island who depend on the sea for their livelihoods. Understanding fishermen’s perceptions of climate change is crucial, as these perceptions influence their adaptation decisions. This study aims to determine the direct and indirect effects of climate change perceptions on the fish catches of Madurese fishermen. The research employed a simple random sampling method with a total of 100 respondents. The results of the path analysis show that fishermen’s perceptions of climate change phenomena have a direct influence on adaptation as well as on fish catches. Perceptions of climate change risks have a direct effect on adaptation but an indirect effect on fish catches through adaptation. Furthermore, adaptation to climate change has a direct impact on fish catches, while climate information and fishermen's experience do not affect either adaptation or fish catches. Therefore, it is necessary to conduct extension activities regarding climate change risks and adaptation strategies. For further research, it is recommended to analyze the factors influencing perceptions of climate change and adaptation.